Produção e nutrição do Panicum maximum BRS Zuri submetido a tipos de ureia - Rocha, Fabiana da (2015)
This study aimed to evaluate the nutritional and productive characteristics of Panicum maximum cv. BRS Zuri by nitrogen fertilization with sources and doses ureas with urease and conventional urea inhibitors on the dry matter production in the shoot and root, number of leaves and tillers, SPAD value, concentration of nitrogen, phosphorus, potassium, calcium, magnesium and sulfur into two growths. The experiment was conducted in a greenhouse located at the Faculty of Agronomy of the Federal University of Mato Grosso, Cuiabá campus, from November 2014 to April 2015. The design was a randomized complete block design with four replications and treatments arranged in a factorial scheme 5x4 + 1 consisting of five nitrogen levels 100, 200, 300, 400 and 500 mg dm-3, four commercial sources of granulated urea: urea (45% N); Urea + NBPT1 (46% N, 0.25% NBPT); Urea + NBPT2 (45% N, NBPT without concentration); Urea + Cu + B (45% N, 015% Cu and 0.4% B), plus the additional witness, which did not apply nitrogen fertilizer, totaling 84 experimental units. Fertilization was divided into three times in the first growth analysis were considered the N doses resulting from the sum of the first two installments 66.7; 133.3; 200.0; 266.7 and 333.3 mg dm-3, while growth in the second N rates of the last installment 33.3; 66.7; 100.0; 133.3 and 166.7 mg dm-3 , all applications ureas were performed on coverage. The interaction of sources and doses of nitrogen did not affect the dry matter production and nutrition of grass BRS Zuri. Nitrogen rates increased the dry matter yield, tillering, leaves, concentration of N, P, K, Ca, Mg, S and SPAD value. The sources ureas influenced the dry matter production of roots, height, leaves, tillering, concentration of P, Ca, Mg and S and SPAD value.